Targeted new membrane addition in the cleavage furrow is a late, separate event in cytokinesis - Shuster, C. B. (The National Academy of Sciences, 2002)
Cytokinesis in animal cells is accomplished in part by an actomyosin contractile ring. Recent work on amphibian, Drosophila, and Caenorhabditis elegans embryos implicates membrane trafficking and delivery as essential for cytokinesis. However, the relative contributions of contractile ring constriction versus membrane insertion to cytokinesis and the temporal relationship between these processes are largely unexplored. Here we monitor secretion of the extracellular matrix protein, hyalin, as a marker for new plasma membrane addition in dividing sea urchin zygotes. We find that new membrane addition occurs specifically in the cleavage furrow late in telophase independent of contractile ring constriction. The directed equatorial deposition of new furrow membrane requires astral microtubules and release of internal stores of Ca(2+), but not the presence of a central spindle. Further, cells arrested in M phase do not secrete hyalin, suggesting that mitotic exit is required for new membrane addition. These results demonstrate that astral overlap in equilaterally dividing cells not only serves to specify positioning and contraction of the contractile ring, but also to direct the delivery of new membrane to the furrow as a late, independent event during cytokinesis.